Draft statutory law "whereby the fundamental right to education is regulated and other provisions are enacted - Varios , Varios (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2024)
Draft statutory law "whereby the fundamental right to education is regulated and other provisions are enacted